ТHЕ ALGORITHM OF ANALYSIS OF AGRICULTURAL RISKS UNDER INFLUENCE OF INCOMPLETE INFORMATION ABOUT THEIR PARAMETERS - L. O. Lomovskykh; O. V. Mandych; O. O. Kovalenko; N. A. Karasova; A. Orzeł (Фінансово-кредитна діяльність: проблеми теорії та практики)
The risk analysis algorithms, which are offered by domestic scientists for Ukrainian farmers, are limited in use and are often obsolete. The situation in agriculture of Ukraine changes quickly enough –new agricultural machinery and new technologies appears, this requires a new management.